A sequência Fedathi na formação matemática do pedagogo: reflexões sobre o ensino de geometria básica e frações equivalentes com o uso do software Geogebra - Santos, Romilson Gomes dos (2015)
This study aimed at analyzing the contributions of the teaching methodology Fedathi Sequence (SF) by using the GeoGebra software, applied in Basic Geometry contents and equivalent fractions in the initial pedagogue training in order to provide favorable conditions for the development of education and learning of mathematics, in a systematic and organized manner. The problematic of the research emerged surrounding the mathematical knowledge of the students in the Pedagogy Course of the Faculty of Education FACED / UFC, research locus, before the use of GeoGebra, in the understanding of the content related to the flat geometric figures; specifically, square, triangle, rectangle and parallelogram and the spatial figures as tetrahedron, cube, octahedron, dodecahedron and icosahedron, and the equivalent fractions. The research was theoretically based on the SF methodology. From the application of Teaching Sessions (SD) promoted by SF, we work in our classes the understanding of math concepts, to provide an investigative learning of knowledge. Therefore, the research problem consisted of the question: How to work the Basic Geometry content and equivalent fractions in mathematics education of pedagogy students, using the GeoGebra from SD? In this sense we opted for the qualitative and quantitative research, using descriptive and exploratory approach, setting up a case study. The investigated subjects were students of the Pedagogy Program. From the observations made in the classroom and the actions of the students during the investigative process, it was possible to identify the categories of research analysis, characterized as: SD and math content on Basic Geometry and equivalent fractions. As data collection technique, we used direct observation, with photos and audio produced during the classes; portfolios and discussion forum in which the activities were recorded in TelEduc virtual environment. The data were submitted to content analysis, considering three stages: pre-analysis, the analytical description of the data and the processing of results, including the inference and interpretation. The results contributed to better understanding of mathematical content in the initial formation of the pedagogue. Therefore, the SF teaching methodology was very important for the use of GeoGebra software as a teaching resource to aid in the formation of mathematics educator, in the assimilation of Geometry Basic content and equivalent fractions.